2019
DOI: 10.1136/bmjopen-2019-030262
|View full text |Cite
|
Sign up to set email alerts
|

Current therapy for the upper limb after stroke: a cross-sectional survey of UK therapists

Abstract: ObjectivesTo survey the reported content, frequency and duration of upper limb treatment provided by occupational and physiotherapists for people after stroke in the UK.DesignA cross-sectional online survey was used. Description and analysis of the data were based on items from the Template for Intervention Description and Replication (Who, Where, What and How much).SettingThe online survey was distributed via professional and social networks to UK-based therapists.ParticipantsRespondents were occupational or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…The most likely reason for a failure to demonstrate functional benefit was that many of our patients may have had severe strokes with a lower potential for recovery 24 and a paucity in the access to an appropriate intensity/dose of rehabilitation for the upper limb. 25 It was, however, reassuring that the early treatment of spasticity with botulinum toxin appears not to have interfered with the recovery of arm function in those who are likely to have had the potential for functional recovery.…”
Section: Discussionmentioning
confidence: 99%
“…The most likely reason for a failure to demonstrate functional benefit was that many of our patients may have had severe strokes with a lower potential for recovery 24 and a paucity in the access to an appropriate intensity/dose of rehabilitation for the upper limb. 25 It was, however, reassuring that the early treatment of spasticity with botulinum toxin appears not to have interfered with the recovery of arm function in those who are likely to have had the potential for functional recovery.…”
Section: Discussionmentioning
confidence: 99%
“…It should also be noted that several studies used RSS with other treatments considered to be usual care or therapy (e.g. motor training) [23], whilst others did not. Combining RSS with targeted motor training could enhance overall benefit by a "priming" effect of RSS upon cortical plasticity which can then be utilized by motor training [11].…”
Section: Discussionmentioning
confidence: 99%
“…For the purposes of this review ESS, RPSS, PNS and PSS were considered to be RSS but the different parameters of delivering RSS were described to elucidate any superiority. Studies where the effects of RSS alone or as an adjunct to usual care/therapy [23] could not be determined, and those using mixed populations/etiologies unless stroke was included and discussed separately, were excluded. Interventions that included functional electrical stimulation, neuromuscular stimulation (e.g.…”
Section: Search Strategymentioning
confidence: 99%
“…In terms of dose, upper limb therapy was reportedly provided for an average of 29 minutes, three times per week. 118 However, this amount exceeds that of observational studies of upper limb treatment. 76,111,119 Recording, measuring and monitoring the treatment received by individuals, and reporting of the rehabilitation services provided, should be integral to routine clinical practice and should not be seen as an added burden.…”
Section: Usual Carementioning
confidence: 96%
“…This finding resonates to some extent with findings from a recent survey of upper limb treatment reported by physiotherapists and occupational therapists across the UK. 118 This survey reported that, although there was considerable variation in treatments provided for stroke patients with severe upper limb deficits, the most common were range of movement exercises, mirror-box therapy and functional electrical stimulation. For those with less severe upper limb deficit, most interventions comprised active, task-specific practice.…”
Section: Usual Carementioning
confidence: 99%